2009
DOI: 10.1038/leu.2009.139
|View full text |Cite
|
Sign up to set email alerts
|

IL-6, but not IFN-γ, triggers apoptosis and inhibits in vivo growth of human malignant T cells on STAT3 silencing

Abstract: STAT1 and STAT3 are the main mediators of the signaling of interferons (IFNs) and of gp130 cytokines, respectively. Neoplastic T lymphocytes frequently become resistant to the IFN-c/ STAT1 apoptotic pathway, often because of the downregulation of the IFN-cR2 receptor chain. Many studies suggest that crossregulation between different STATs, in particular between STAT1 and STAT3, may profoundly affect cytokine/growth factor signaling. Here, the function of STAT3 in the negative regulation of STAT1 apoptotic path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 27 publications
2
26
1
Order By: Relevance
“…We found that changing the STAT3 level did not significantly affect the state of STAT1* after IFN-gamma stimulation (Figure 3A), which was consistent with previous experimental observations [22]. By contrast, the level of STAT1* was clearly affected by the initial STAT3 concentration in response to IL-6.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We found that changing the STAT3 level did not significantly affect the state of STAT1* after IFN-gamma stimulation (Figure 3A), which was consistent with previous experimental observations [22]. By contrast, the level of STAT1* was clearly affected by the initial STAT3 concentration in response to IL-6.…”
Section: Resultssupporting
confidence: 91%
“…Costa-Pereira et al showed that IL-6 mediated an IFN-gamma-like response in mouse embryo fibroblasts lacking STAT3, including the prolonged activation of STAT1 and it promoted the induction of multiple IFN-gamma-inducible genes [20]. However, Regis et al reported that the activation of STAT1 in human neoplastic T lymphocytes after IFN-gamma stimulation was generally unaffected by STAT3 silencing [22]. Ho et al argued that STAT3 did not affect the activation of STAT1 [23].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary experiments have indicated that sustained STAT1 phophorylation in ST4 cells expressing mutated IFN-␥R2 persisted until 24 h IFN-␥ stimulation. This long lasting IFN-␥-induced phophorylation of STAT1 was also observed in ST4 cells devoid of STAT3 [41].…”
Section: Discussionmentioning
confidence: 90%
“…The plasmids pCMVD8.2 (GAG-POL DNA), the vesicular stomatitis virus (VSV-G) envelope plasmid pMD.G and gene transfer plasmid pLVTH were provided by Dr. Ralph B. Arlinghaus at the University of Texas. The STAT3 shRNA sequence and the nontargeting sequence used in this study were synthesized, according to the published sequence [39]. The PC3M-1E8 cells were infected with lentiviruses in the presence of 8 μg/ml of polybrene (Sigma Chemical Co., St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%